Ensino do gênero oral na escola: a prática do seminário - Menezes, Leandro Freitas (Linguagens & Cidadania, 2017)
The textual genres are important because of being the way for which communicates. It is noticed in this sense, meantime, that the oral types are more worn-out in the daily life and the written ones least taught in the schools, specially form them like the seminar, which they have a great usefulness and are not dominated by perfection by the pupils. In this form, the seminar shows up to be worked in a proposal of educational sequence aiming at the upgrading of the students.